Variations of distance and accelerometry-based GPS measures and their influence on body composition in professional women soccer players - Fernandes, R.; Martins, A. D.; Clemente, F. M.; Brito, J. P.; Nobari, H.; Reis, V.; Oliveira, R. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2025)
External intensity quantification and body composition assessments across the season allow soccer coaches to adjust the intensity during training sessions, thereby avoiding excessive fatigue and helping players maximize their physical fitness status during matches. Thus, the aims of this study were (1) to describe variations in external intensity periods of distance and accelerometry-based measures across the early and mid-competitive phases and (2) to analyze whether the intensity variations influenced body composition across the 2019/20 competitive season. Ten players from a Portuguese BPI Ligue team (professional league) participated in this study. The participants completed =80% of 57 training sessions and 13 matches. The athletes were assessed in three phases (before the start of the season, after 2 months, and after 4 months) for the following variables: body fat mass, soft lean mass, fat-free mass, intracellular water, extracellular water, total body water, and phase angle (50 kHz) through bioelectrical impedance analysis (InBody S10). A 10-Hz GPS device (PlayerTek) was used to collect distance and accelerometry-based measures, which included total distance, high-speed running distance, sprint distance, acceleration, deceleration, and player load. Repeated-measures analysis of covariance (ANCOVA) with GPS-derived measures as covariates or repeated-measures analysis of variance (ANOVA) was used to compare the three moments of assessment. Although the patterns of variables` responses were not the same as the season progressed, the values of body fat mass, fat-free mass, intracellular water, extracellular water, total body water, ratios of ECW/TBW, ECW/ICW, and phase angle improved. Variations in external intensity measures seem to influence the body composition variables across the season. These results may indicate good adaptations to the training and conditioning strategies managed by the coach and technical staff.